Women and narrative identity : rewriting the Quebec national text - Green, Mary Jean Matthews (McGill-Queen's University Press, 2001)
In Women and Narrative Identity Green demonstrates that the "national text" has at times functioned to constrain women's literary expression, while in other cases it has empowered the feminine voice, endowing it with a unique identitary power. She shows that writers such as Laure Conan, Germaine Guèvremont, Gabrielle Roy, Anne Hébert, and Marie-Claire Blais have been recognized as important because they have been widely perceived as speaking to and about the people of Quebec. The Quebec identity narrative has offered women writers a framework within which they are able not only to make their voices heard but to tell a story of feminine dispossession and desire that often questions central cultural values. Green shows that while women writers in Europe and America have subtly altered the form of the novel, in Quebec women have, in rewriting the narratives of Quebec identity, also redefined the terms of the nation itself.